Difundindo direitos, coletivizando justiça : O ministério público como organização aprendente - Sousa, Jonatha Vieira de (2014)
The twentieth century is a milestone in the creation and development of policies, strategies and areas of knowledge in organizational settings, particularly to monitor the process of ongoing globalization and affects relationships of various kinds, whether economic, social, cultural or learning . In this context, this work is a result of research, project whose objective was to understand the politics of teacher education developed by the Public Ministry of Paraíba (MPPB), citing the following question: how to structure the policy of continuing education in the Ministry public Paraíba? In methodological terms, was first made field research, funded by the qualitative and quantitative approach, the documentary and descriptive, using a mixed questionnaire as instruments for data collection, streamlining the organization and interpretation of the results in light of the content analysis . The universe of 490 subjects aged Attorneys, Prosecutors and Public Servers Ministry of Paraíba, who work throughout the state, 94 comprised the sample as research subjects, with 32 members (Attorneys and Prosecutors) and 62 servers, whom we sought relevant information about continuing education to which they are subjected. The survey results showed that prosecutors Paraíba presents the following table: tends to favor the continuing education of members; under-utilizes digital technologies of information and communication to promote continuing education; 71.88% and 62.90% of the members of the servers showed dissatisfaction about the courses process. After 2010, it is emphasized that 74.20% of the servers did not participate in training courses, and 68.75% of members participated in the training program. For members, there was a contradiction in the purpose of qualification, considering that undergo this process as a means to derive functional advantage transfer exams and merit promotion. For servers, there was a disincentive to participation, given that the organization has no regulation which recognizes those who undergo continuous training. As a result of emphasis from technical and applied design, qualification to participate in the formalization of agreements and technical cooperation between public and private institutions agreements, as well as the implementation of a new guideline for functional servers, as the plan for jobs , careers and remuneration, focusing on designing an organization that purports to be a learner.